Islamic diplomatic mechanism in Malay Sultanate letter - Noor Muhammad, Salmah Jan (Human Resource Management Academic Research Society, 2018)
Malay Sultanate letter is Jawi hand-written text that possesses the splendid and attractive illmumination. It was incumbent upon the goverment officials to send it to the other governments. This letter was authored by a palace writer as in tandem with the missions of the monarch of the kingdom. Often time, through this letter, the monarch has come to an agreement to establish a diplomatic relation. In this sense, the question that might be raised is that what ‘s interesting and the highlight of the Malay Sultanate letter that capables of establishing a diplomatic relationship between kingdoms? Through the meticulous observations upon some selected letters from Malay Sultanate, the most apparent things figured out was the arrangement of letter contents that bear the Islamic doctrine elements. Therefore, the objective of this study is to identify and describe the Islamic diplomatic mechanism that was practiced by the government officials to establish diplomatic relationship with other governments. Hence, this research finding is hopefully meaningful and helpful to all political science and diplomatic relation institution reseachers in approaching the study of international relation practices in ancient governments.